ANALISIS KINERJA KEUANGAN DENGAN RASIO LIKUIDITAS, RASIO SOLVABILITAS, RASIO AKTIVITAS, RASIO PROFITABILITAS DAN RASIO PASAR PT. ASTRA INTERNASIONAL Tbk PERIODE 2017-2021 - Wiyati, Rita; Salmiah, Neneng; Juwita, Intan (Komunitas Manajemen Kompetitif, 2023)
In analyzing the financial reports at PT Astra International, Tbk. using descriptive analysis methods and data collection techniques using library research. Based on data from the financial position report and profit and loss report, changes in capital and balance sheet at PT. Astra International, Tbk from 2017 to 2021, shows that the financial condition of this company is generally very good. The level of activity of this company is very good in managing its trade receivables. The level of solvency of this company in the first year is not able to manage its long-term obligations. The level of profitability. This company is very good, it can be seen from the company's ability to generate net profit and the level of market value ratio. This company can be seen very well from the company's ability to increase the value of its share price.